Public Spending Management and Macroeconomic Interdependence - Ganelli, Giovanni (IMF Working Papers; Working Paper ;, 2004)
This paper studies, in the context of a New Open Economy Macroeconomics (NOEM) model, the effects of "public competition policies" aimed at improving the efficiency of public spending. Such measures are modeled as an increase in the price elasticity of public consumption. The paper finds that public competition policies significantly affect macroeconomic interdependence across countries. Following a domestic fiscal expansion, an higher public price elasticity increases the substitutability between goods purchased by the domestic and the foreign governments. The same exchange rate variation can therefore sustain larger shifts in relative demand for goods. The expenditure-switching effect is magnified, implying a larger change in relative output. In welfare terms, countries with a larger government sector have an incentive to promote public competition policies.